2021
DOI: 10.3390/biom11070973
|View full text |Cite
|
Sign up to set email alerts
|

New Hybrid Compounds Combining Fragments of Usnic Acid and Monoterpenoids for Effective Tyrosyl-DNA Phosphodiesterase 1 Inhibition

Abstract: Usnic acid (UA) is a secondary metabolite of lichens that exhibits a wide range of biological activities. Previously, we found that UA derivatives are effective inhibitors of tyrosyl-DNA phosphodiesterase 1 (TDP1). It can remove covalent complex DNA-topoisomerase 1 (TOP1) stabilized by the TOP1 inhibitor topotecan, neutralizing the effect of the drugs. TDP1 removes damage at the 3′ end of DNA caused by other anticancer agents. Thus, TDP1 is a promising therapeutic target for the development of drug combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…DCA derivatives 1-18 were docked into the binding site of the TDP1 (PDB ID: 6W7K, resolution 1.70 Å) [35] and TDP2 (PDB ID: 5J3S, resolution 3.40 Å) [36] enzymes. The robustness of the TDP1 docking scaffold has been previously established [19]; the robustness of the TDP2 docking scaffold was confirmed and further discussion (see Supplementary Materials, Molecular modeling section).…”
Section: Molecular Modelingsupporting
confidence: 65%
See 2 more Smart Citations
“…DCA derivatives 1-18 were docked into the binding site of the TDP1 (PDB ID: 6W7K, resolution 1.70 Å) [35] and TDP2 (PDB ID: 5J3S, resolution 3.40 Å) [36] enzymes. The robustness of the TDP1 docking scaffold has been previously established [19]; the robustness of the TDP2 docking scaffold was confirmed and further discussion (see Supplementary Materials, Molecular modeling section).…”
Section: Molecular Modelingsupporting
confidence: 65%
“…Molecular dynamics simulations have suggested that the TDP1 inhibitors occupy an allosteric binding pocket next to the catalytic site, as shown in Figure 4 A [ 18 ]. The existence of the allosteric site was further supported by combined molecular modeling and structural activity relationship study of usnic acid derivatives, combined with monoterpenoids [ 19 ]. The occupancy of the allosteric site was shown to be very advantageous to the overall binding efficacy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that Tdp1 knockout cells were more sensitive to Tpc compared to WT cells. The data on the HEK293FT mutants were of low reproducibility [48], which is why we decided to change the basic cell line to HEK293A [49]. In this work, we created new PARP1-/-HEK293A cells using the CRISPR-Cas9 approach (Figure S27).…”
Section: Tdp2 Activity In the Presence Of Tdp1 Inhibitorsmentioning
confidence: 99%
“…In our previous works, we checked the cytotoxic effect of Tpc and the TDP1 inhibitors -monoterpene 3-carene-derived compounds [48,49] and UA combined with monoterpenoids [49], measured separately and jointly with Tpc-using a panel of HEK293FT and HEK293A Tdp1 knockout isogenic clones. We showed that Tdp1 knockout cells were more sensitive to Tpc compared to WT cells.…”
Section: Tdp2 Activity In the Presence Of Tdp1 Inhibitorsmentioning
confidence: 99%